Pengembangan Daerah Pertanian Lahan Kering dalam Upaya Penyediaan Air Dangkal dan Irigasi Teknis di Desa Margaasih - Irmawatie, Lilis; Maulana, Dickdick; Adviany, Ida; Supriatna, Asep; Suswana, Suli (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
After the Covid-19 pandemic, it has had a significant impact among the farming community or farm workers in Margaasih Village, Cicalengka District, Bandung Regency. In his upanya improves socioeconomic capabilities and regional development based on existing local wisdom, then, the community service program organized by the Faculty of Agriculture, Universitas Islam Nusantara in collaboration with PT. State Electricity Company West Java Distribution Unit in the TJSL-CSR or Community Development program with the theme "Agriculture Electrifying". This service activity program aims to increase this potential in Margaasih Village through the Mainstay Farmer Group "Tani Sugih Mukti". The use of bamboo leaf compost has been well implemented in the previous service program on vines. The expansion of the development of potential locations and commodity bases in assisted villages is expected to improve socioeconomic conditions in other undeveloped commodities in the region. Dry land that is usually cultivated in the dry season can be changed by adding a few technological factors such as the procurement of deep-water sources and irrigation techniques so that the conversion of cultivation from corn crops to short-term cultivated crops such as horticultural crops (bokor lettuce, kale, eggplant, chili, cucumber, etc.). This program is projected to increase the productivity of farming businesses which ultimately increases income and welfare in a sustainable manner as well as other agricultural options during the dry month in Margaasih Village. This is evidenced by the calculation of Social Return on Investment (SROI) Prediction for 3 months of 0.71 and land use of 1540 m2